2017
DOI: 10.1002/hbm.23701
|View full text |Cite
|
Sign up to set email alerts
|

Pivotal role of hMT+ in long‐range disambiguation of interhemispheric bistable surface motion

Abstract: It remains an open question whether long-range disambiguation of ambiguous surface motion can be achieved in early visual cortex or instead in higher level regions, which concerns object/surface segmentation/integration mechanisms. We used a bistable moving stimulus that can be perceived as a pattern comprehending both visual hemi-fields moving coherently downward or as two widely segregated nonoverlapping component objects (in each visual hemi-field) moving separately inward. This paradigm requires long-range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 101 publications
(157 reference statements)
6
19
0
Order By: Relevance
“…There is single-cell electrophysiological evidence that neuronal computation of global 2-D or pattern motion is performed by such pattern selective neurons in hMT+, while neurons in early visual cortex, such as V1 and V2, are only sensitive to 1-D motion features of an object (virtually 100% of component motion neurons in these regions) 18,19 . It is therefore not expected that V1 and V2 differentially respond to stimuli requiring perceptual integration, as we have verified in our previous studies 13,15 .…”
Section: Introductionsupporting
confidence: 67%
See 4 more Smart Citations
“…There is single-cell electrophysiological evidence that neuronal computation of global 2-D or pattern motion is performed by such pattern selective neurons in hMT+, while neurons in early visual cortex, such as V1 and V2, are only sensitive to 1-D motion features of an object (virtually 100% of component motion neurons in these regions) 18,19 . It is therefore not expected that V1 and V2 differentially respond to stimuli requiring perceptual integration, as we have verified in our previous studies 13,15 .…”
Section: Introductionsupporting
confidence: 67%
“…This allows us to specifically investigate the role of the hMT+ interhemispheric functional connectivity in the modulation of surface segregation vs. integration as a probe to investigate the role long-range interactions in decision. In a previous study we observed that long-range binding of this bistable stimulus mainly reflect bottom-up processes arising within hMT+ 13 . As a step further, we set to investigate with high-resolution (7T) functional magnetic resonance imaging (fMRI), the role of interhemispheric functional connectivity across hMT+ in both hemispheres as a modulator of perceptual integration vs. segregation of multiple physically constant moving surfaces separated across hemifields.…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations